Mediate evaluation of replicating a Training Program in Nonverbal Communication in Gerontology - Schimidt, Teresa Cristina Gioia; Duarte, Yeda Aparecida de Oliveira; Silva, Maria Julia Paes da (Revista da Escola de Enfermagem da USP, 2015)
OBJECTIVE Replicating the training program in non-verbal communication based on the theoretical framework of interpersonal communication; non-verbal coding, valuing the aging aspects in the perspective of active aging, checking its current relevance through the content assimilation index after 90 days (mediate) of its application. METHOD A descriptive and exploratory field study was conducted in three hospitals under direct administration of the state of São Paulo that caters exclusively to Unified Health System (SUS) patients. The training lasted 12 hours divided in three meetings, applied to 102 health professionals. RESULTS Revealed very satisfactory and satisfactory mediate content assimilation index in 82.9%. CONCLUSION The program replication proved to be relevant and updated the setting of hospital services, while remaining efficient for healthcare professionals.